The Effectiveness of Distance Learning Media Based on Augmented Reality Technology on Covalent Bonding Material For Class X at SMAN 1 Dawarblandong - Mohamad Nurkholik (Universitas Lampung, 2021)
Abstract: The Effectiveness of Distance Learning Media Based on Augmented Reality Technology on Covalent Bonding Material For Class X at SMAN 1 Dawarblandong. The purpose of this research was to determine the effectiveness of learning media based on augmented reality technology in covalent bonding in terms of learning outcomes and student motivation in class X-IPA 1 SMAN 1 Dawarblandong. The research method used is One Group Pretest-Postest Design. The data obtained in this study obtained the following data: student learning outcomes have increased. This can be seen from the value of the pretest and posttest with the acquisition of N-Gain of 0.84 in the high category and 0.61 in the medium category. Meanwhile, student learning motivation obtained from the response questionnaire obtained an average result of 83.975 with the predicate very effective. This proves that teaching materials based on augmented reality technology in covalent bonding material are declared effective as a medium for learning chemistry Keywords: Augmented Reality, Covalent Bonding, Motivation to Learn.